The Bob Dylan albums - Varesi, Anthony (Essential essays series, 2022)
"Since the first edition of The Bob Dylan Albums appeared in 2002, there have been seven new Bob Dylan studio albums and fifteen archival collections. The latter have included the complete studio recordings for the famed 1965-1966 sessions, the entirety of the Basement Tapes recordings, a Blood on the Tracks box set and several complete concerts from the 1975 Rolling Thunder Revue, released to coincide with director Martin Scorsese's acclaimed 2019 film Rolling Thunder Revue. And 2022 marks the 60th anniversary of the release of Dylan's first studio album. Dylan's body of work is vast; this second edition is the most complete and up to date study of all of Dylan's official albums, presented in an accessible, highly readable fashion."